Chapter 3 Sickness, disease and medical practitioners in 1640s Ireland - Cunningham, John (Social Histories of Medicine, 2019)
This chapter explores the medical environment of 1640s Ireland, particularly during the 1641 Rebellion. It uses the 1641 Depositions to explore how people understood reported sickness and disease. It also traces the experiences of a broad range of medics during a period of warfare and significant social and political upheaval. In doing so, it enables an important new perspective on medicine in Early Modern Ireland.